Performance Characterization of Random Pulse Width Modulation Algorithms in Industrial and Commercial Adjustable-Speed Drives - Lee, Kevin; Guangtong Shen; Wenxi Yao; Zhengyu Lu (IEEE transactions on industry applications, 2017)
One of the problems of the pulse-width-modulation (PWM)-controlled ac machines is the acoustic noise that could become unacceptable when used in sensitive environments. Random PWM (RPWM) in industrial and commercial adjustable-speed drives (ASD) results in the partial transfer of power from the discrete spectrum (narrowband noise) of the output voltage to the continuous spectrum (wideband noise), with advantageous effects on reducing the acoustic noise in the motor drive system. In this paper, the theoretical power spectrum analysis as the basis for RPWM is presented. Five state-of-the-art RPWM strategies, their voltage, current, and acoustic noise spectra characteristics are quantitatively evaluated. The PWM schemes and theoretical analysis are validated through a 2.2-kW 380-V 50-Hz ASD induction machine experimental setup. The results provide valuable data for practicing engineering community to choose the best option in real-world applications.